Involuntary Cognitions in Everyday Life: Exploration of Type, Quality, Content, and Function - Krans, Julie; de Bree, June; Moulds, Michelle L. (Frontiers in Psychiatry, 2015)
Psychological research into spontaneous or intrusive cognitions has typically focused cognitions in one predefined domain, such as obsessional thoughts in OCD, intrusive memories in PTSD and depression, or involuntary autobiographical memories and daydreaming in everyday life. Such studies have resulted in a wealth of knowledge about these specific cognitions. However, by focusing on a predefined type of cognition, other subtypes of cognition that may co-occur can be missed. In this exploratory study we aimed to assess involuntary cognitions in everyday life without a predetermined focus on any specific subtype of cognition. Seventy unselected undergraduate student participants were administered a questionnaire that assessed the presence of any involuntary cognitions in the past month, their quality, type, content, and potential function. In addition, participants provided self-descriptions and completed measures of psychopathology. Content analyses showed that involuntary cognitions were common, predominantly visual in nature, emotional, often about social relationships, and often related to a hypothetical function of emotional processing. About two-thirds of the cognitions that participants reported were memories. Non-memories included daydreams, imaginary worst case scenarios, imaginary future events, hypothetical reconstructions, and ruminations. Memories and non-memories were strikingly similar in their subjective experience of content and emotionality. Negative (but not positive) self-descriptions were positively related with negative involuntary cognitions and psychopathology, suggesting a link between involuntary cognitions and the self. Overall, the findings suggest that people experience a wide variety of subtypes of involuntary cognitions in everyday life. Moreover, the specific subtype of involuntary cognition appears to be less important than its valence or content, at least to the subjective experience of the individual.